Proof-of-concept fabrication of carbon structure in Cu–N–C catalysts of both high ORR activity and stability. (15th April 2021) - Han, Guokang; Li, Lingfeng; Li, Xudong; Sun, Yongrong; Du, Chunyu; Gao, Yunzhi; Yin, Geping
Abstract: N-doped hierarchical carbon (NHC) composed of hierarchically arranged highly graphitic graphene shells with high surface/bulk ratio is demonstrated as a proof of concept, and utilized as carbon source in Cu–N–C catalysts. The special structure is contributed to Fe nanoparticles induced to PANI nanospheres, which serving as hard templates greatly alter the thermal decomposition/carbonization process of PANI. When employed as carbon source in Cu–N–C ORR catalyst, not only is the catalytic activity boosted as a result of highly loaded Cu centers anchored at the rather accessible sites to oxygen, the stability is greatly enhanced as well. Graphical abstract: Image 1 Highlights: Iron oxides alters the decomposition/carbonization process of PANI. Hierarchically arranged graphene shells grants NHC with high surface/bulk ratio. High surface/bulk ratio of NHC shows advantage in Cu anchoring. Cu–NHC presents both high ORR activity and satisfying stability.